(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Joint injuries represent a significant portion of musculoskeletal disorders worldwide, affecting individuals of all age groups, particularly athletes and the elderly. These injuries range from mild ligament sprains to severe cartilage damage and joint dislocations. With advancements in medical science, innovative approaches such as regenerative medicine, minimally invasive surgery, and biomechanical rehabilitation have significantly improved treatment outcomes. This article explores the types, causes, and mechanisms of joint injuries, and analyzes modern therapeutic strategies, including stem cell therapy, platelet-rich plasma (PRP), arthroscopy, and digital rehabilitation technologies. The study highlights the effectiveness of these innovations in accelerating recovery, reducing complications, and improving long-term joint function.